Obstetric haemorrhage and risk of cardiovascular disease after three decades: a population‐based cohort study. (28th June 2020) - Ukah, UV; Platt, RW; Potter, BJ; Paradis, G; Dayan, N; He, S; Auger, N
Abstract : Objective: To investigate the association between obstetric haemorrhage and cardiovascular disease up to three decades after pregnancy. Design: Population‐based cohort study. Setting and population: All women who delivered between 1989 and 2016 in Quebec, Canada. Methods: Using hospital admissions data, 1 224 975 women were followed from their first delivery until March 2018. The main exposure measures were antenatal (placenta praevia, placental abruption, peripartum haemorrhage) or postpartum haemorrhage, with or without transfusion. Adjusted Cox regression models were used to assess the association between obstetric haemorrhage and future cardiovascular disease. Main outcome measure: Cardiovascular hospitalisation. Results: Among 104 291 (8.5%) women with haemorrhage, 4612 (4.4%) required transfusion. Women with haemorrhage had a higher incidence of cardiovascular hospitalisation than women without haemorrhage (15.5 versus 14.1 per 10 000 person‐years; 2437 versus 28 432 events). Risk of cardiovascular hospitalisation was higher for obstetric haemorrhage, with or without transfusion, compared with no haemorrhage (adjusted hazard ratio [aHR] 1.06, 95% CI 1.02–1.10). Women with haemorrhage and transfusion had a substantially greater risk of cardiovascular hospitalisation (aHR 1.47, 95% CI 1.23–1.76). Among transfused women, placental abruption (aHR 1.79, 95% CI 1.06–3.00) and postpartum haemorrhage (aHR 1.38, 95% CI 1.13–1.68) were both associated with risk of cardiovascular hospitalisation. Antenatal haemorrhage with transfusion was associated with 2.46 times the risk of cardiovascular hospitalisation at 5 years (95% CI 1.59–3.80) and 2.14 times the risk at 10 years (95% CI 1.47–3.12). Conclusions: Obstetric haemorrhage requiring transfusion is associated with maternal cardiovascular disease. The benefit of cardiovascular risk prevention in pregnant women with obstetric haemorrhage requires further investigation. Tweetable abstract: Risk of future cardiovascular disease is increased for women with obstetric haemorrhage who require transfusion. Tweetable abstract: Risk of future cardiovascular disease is increased for women with obstetric haemorrhage who require transfusion.